The complete chloroplast genome sequence of Brachybotrys paridiformis Maxim. ex Oliv. (Boraginaceae), a species from a monotypic genus in Northeast China - Yang Liu; Hao Dong; Linghong Li; Siyu Ding; Zhi Zang; Xi Lu (Mitochondrial DNA. Part B. Resources, 2025)
Brachybotrys paridiformis is well known for its remarkable medicinal properties. Here, the complete chloroplast genome of B. paridiformis was assembled and annotated. The genome was 147,853 bp in size contained a large single-copy region (80,375 bp), a small single-copy region (17,184 bp), and a pair of inverted repeat regions (25,147 bp), respectively. It comprised 128 genes, including 83 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis revealed that Brachybotrys and Trigonotis are phylogenetically closely related. The findings of this study provide valuable information for phylogenetic and evolutionary research on Boraginaceae.